Neuropathic pain in individuals with sickle cell disease. (1st January 2020) - Sharma, Deva; Brandow, Amanda M.
Abstract: Pain is the most frequently occurring complication of sickle cell disease (SCD) and the leading cause of hospitalizations for affected individuals. Acute pain episodes are also an independent predictor of mortality in individuals with SCD. The pathophysiology of pain in SCD is complex and has been attributed to several biologic factors, including oxidative stress, vaso-occlusion, ischemia-reperfusion injury and inflammation. In spite of this complex biology, painful events requiring hospitalization are simplistically referred to as "acute vaso-occlusive pain episodes" by the hematology community, and subgroups of pain in SCD have not been formally classified. Neuropathic pain is an emerging and unique SCD pain phenotype that could be a result of these biologic drivers in SCD. Neuropathic pain is caused by a lesion or disease of the somatosensory nervous system and has been estimated to occur in approximately 25–40% of adolescents and adults with SCD. Diagnostic modalities for neuropathic pain, including validated questionnaires incorporating pain descriptors, quantitative sensory testing and functional neuroimaging, have been evaluated in small to medium-sized cross-sectional studies of adolescents and adults with SCD. However, these diagnostic tests are not currently used in the routine care of individuals with SCD. Age, female gender and hydroxyurea use have been reported to be positively associated with neuropathic pain in SCD, although modifiable risk factors for the prevention of neuropathic pain in this population have not been identified. A few early phase studies have begun to investigate neuropathic pain-specific medications in individuals with SCD. However, evidence-based strategies to target neuropathic pain in SCD are lacking, and the existing literature suggests that neuropathic pain-specific medications are highly underutilized in individuals with SCD. We will review the epidemiology, underlying biology and therapeutic interventions for diagnosis and treatment of neuropathic pain in SCD. We will also highlight opportunities to address critical gaps in knowledge that remain for this under-recognized cause of SCD morbidity.